(untitled) (Periphērica, 2020)
Lope (Andrucha Waddington 2010) and Teresa (Ray Loriga 2007) have much in common. Both biopics center on a revered literary figure of the Spanish Golden Age. However, in spite of their many commonalities, these films embody two distinct tendencies in the contemporary literary biopic genre: one more “typical,” represented by Lope, that focuses heavily on plot development and another, represented by Teresa, that aspires to visually transpose to the screen aspects that relate to the main character’s interiority. Although Teresa has features of the “typical” contemporary literary biopic, it innovates the genre significantly by moving its focus from the life to the mind of the writer. Loriga uses the language of cinematography to depict the imagery and affective qualities of the mysticism of Teresa de Ávila—the force behind her writings—, creating a film that emphasizes image and emotions over plot. Teresa thus brings a different sensitivity to the literary biopic, which deviates from more formulaic films. Centering on the author’s mind can indeed be a new path for filmmakers to innovate the biopic genre, particularly in its literary strand. Finally, these two biopics illustrate the need to expand the scholarly conversation about the contemporary literary biopic genre, as they both engage with and deviate from the formula established by Anglo-Saxon biopics.